The American language of rights - Primus, Richard A. (Ideas in context ;, 1999)
This examination of three crucial periods in American history (the late eighteenth century, the civil war and the 1950s and 1960s) demonstrates how the conceptions of rights prevailing at each of these times grew from opposition to specific political adversities. This study will be a major contribution to political theory.